Mystery on October Road - Herzig, Alison Cragin; Mali, Jane Lawrence (New York : Viking, 1991)
When a mysterious masked man moves into the house next door, ten-year-old Casey and her friends, Cats and Benny, are determined to find out more about him.
Keywords: Friendship -- Fiction; Mystery and detective stories